(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
Neoplatonism in Spanish Literature is a particularly interesting subject as the resurgence and reinterpretation of Plato’s ideas were basic to the ideology and aesthetic conception of the Renaissance. Neoplatonism influenced the diverse genres of the age. Its ideological effect can be seen in the pastoral novel and the literature of chivalry, as well as in lyric poetry, mystical poetry and Spanish Renaissance theatre. The idea of love and the concept of nature are the most important neoplatonic elements found in the literature. These themes are explored in an attempt to discover exactly how they influenced the different genres and the most distinguished writers of the period.